PENINDASAN RAS KULIT PUTIH EROPA TERHADAP RAS KULIT HITAM AFRIKA DALAM CERPEN â€œA BLACK-SKINNED GIRLâ€ KARYA SEMBENE OUSMANE (Kajian Pendekatan Poskolonial) - Hadiyanto Hadiyanto (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2008)
Colonialism continuously brings about the complexity of excess either to the colonizing country or the colonized country. This essay discusses the post-colonialism effect on African society reflected in Sembene Ousmaneâ€™s A Black Skinned Girl. It tells an African black skinned-girl with her obsession to be a successful housemaid in France, yet living a life in misery and sorrows she has passed through every day as a result of her mistressâ€™s colonial conduct. The European white-skinned woman does such a cruel treatment to the African black skinned-girl since she thinks that she has a very dissenting cultural and racial identity. Anti-colonial resistance done by the African black skinned-girl really means nothing, not changing the heart-breaking fate but her death. Not merely oppression, but also African natural resource richness that her white-skinned master and mistress have already exploited.